Mercury transport and resistance. (August 2002) - Brown, N. L.; Shih, Y.-C.; Leang, C.; Glendinning, K. J.; Hobman, J. L.; Wilson, J. R.
Abstract : Resistance to mercuric ions in bacteria is conferred by mercuric reductase, which reduces Hg(II) to Hg(0) in the cytoplasmic compartment. Specific mercuric ion transport systems exist to take up Hg(II) salts and deliver them to the active site of the reductase. This short review discusses the role of transport proteins in resistance and the mechanism of transfer of Hg(II) between the mercury-resistance proteins.